Water science under the global epidemic of COVID-19: Bibliometric tracking on COVID-19 publication and further research needs. Issue 4 (August 2021) - Ji, Bin; Zhao, Yaqian; Wei, Ting; Kang, Peiying
Abstract: There are overwhelming increases of studies and over 200, 000 publications related to all the aspects of COVID-19. Among them, 262 papers were published by authors from 67 countries regarding COVID-19 with water science and technology. Although the transmission routes of SARS-CoV-2 in water cycle have not been proved, the water and wastewater play an important role in the control of COVID-19 pandemic. Accordingly, it is scholarly relevant and interesting to look into publications of COVID-19 in water science and technology to track the investigations for moving forward in the years to come. It is believed that, through the literature survey, the question on what we know and what we do not know about COVID-19 so far can be clear, thus providing useful information for helping curbing the epidemic from water sector. This forms the basis of the current study. As such, a bibliometric analysis was conducted. It reveals that wastewater-based epidemiology (WBE) has recently gained global attention with the source and survival characteristics of coronavirus in the aquatic environment; the methodology of virus detection; the water hygiene; and the impact of the COVID-19 pandemic on the water ecosystem being the main topics in 2020. Various studies have shown that drinking water is safety whereas wastewater may be a potential risk during this pandemic. From the perspective of the water cycle, the scopes for further research needs are discussed and proposed, which could enhance the important role and value of water science in warning, monitoring, and predicting COVID-19 during epidemic outbreaks. Graphical Abstract: ga1 Highlights: 262 papers published by authors of 67 countries/regions regarding COVID-19 with water science and technology in 2020. Two research trends of source & survival characteristics and the methodology of virus detection. Further research needs of standardized protocol for WEB and secondary risk for water health. The digital revolution in water industry being helpful for COVID-19 control.